Pakan Alami dan Habitat Kukang (Nycticebus coucang) dan . Tarsius (Tarsius bancanus) Di Kawasan Hutan Pasir Panjang, Kalimantan Tengah - Wirdateti, Wirdateti (Perhimpunan Biologi Indonesia, 2005)
ABSTRACTFeeds and habitat utilization of Slow Loris (Nycicebus coucang) and Tarsier (Tarsiusbnncartus) in Pasir Panjang Forest, Central Kalimantan. This research was conducted inthe production forest of Saka and Padang Babuluh in Pangkalan Bun. Study sites werelocated at 9-42 m above sea level. Data being collected were the type of feed, nest sites andhabitat utilization. During the observation, 44 plants species from 17 families were identifiedbeing consumed and nest site by the slow lories. Twenty one species from 17 families wereidentified being habitat by the tarsier. Nest were built on growing trees and litters were usedas bedding.Keywords : Nycticebus coucang, Tarsius bancanus, feeds, habitat, Pasir Panjang Forest